Social Institutions in the Qur'an: Ethics and Culture of Student Association Ali Ash-Shabuni's Perspective in the Book of Rawa'iul Bayan - Husna, Rifqatul; Ghaits, Qatrul (Jurnal Sustainable, 2023)
This research was motivated by the increasing lack of akhlakul karimah in the character of Indonesian Muslims. They commit acts forbidden in Islam, even to the level of adultery. The purpose of the study was to explain how a person should be ethical and get along correctly from the perspective of Ali Ash-Shabuni. The research method in this article uses qualitative research methods with the type of library research and uses the maudhu'i method, namely by collecting several related verses. The analysis used is descriptive-analysis. Data collection techniques are by collecting data and information such as journals, papers, books, news and other reading sources, especially in the book of Rawa'iul Bayan. The result of the study is that the ethics of association of the opposite sex who are not mahram are divided into six, first do not look at those that can cause slander. Second, do not make physical contact. Third, it is not lonely unless the woman is accompanied by a mahram. Fourth, do not speak which can cause slander. Fifth, for women Islam recommends wearing clothing that covers the entire body except the face and palms. Sixth, Islam forbids women to travel for a day and night without a mahram. In addition, there are three times that are highly recommended to ask permission when entering one's house or room, namely at dawn, the time after Dhuhr and after Isya', because at these times a person is vulnerable in a state of opening the aurat, resting, even being naked.